Agricola ; and Germany - Tacitus, Cornelius; Birley, Anthony Richard; Tacitus, Cornelius (Oxford ; New York : Oxford University Press, 1999)
"Cornelius Tacitus, Rome's greatest historian and the last major writer of classical Latin prose, produced his first two books in AD 98. He was inspired to take up his pen when the assassination of Domitian ended 'fifteen years of enforced silence'. These first products were brief: the biography of his late father-in-law Julius Agricola and an account of Rome's most dangerous enemies, the Germans. As governor for seven years, Agricola had completed the conquest of Britain and much of Tacitus' biography is devoted to the country and its people. Germany is the only surviving specimen from the ancient world of an ethnographic study. Each of these early works has had immense influence on our perception of Rome and the northern 'barbarians'." "This newly translated edition reflects recent research in Roman-British and Roman-German history, including recently discovered evidence on Tacitus' early career."--Jacket
The life of Agricola -- The origin and land of the Germans.
Includes bibliographical references and indexes.
Print version record.
Translated from the Latin.
eBooks on EBSCOhost
Keywords: Agricola, Gnaeus Julius, -- 40-93.; Agricola, Gnaeus Julius, -- 40-93; Tacitus, Cornelius; Agricola; Germania; Statesmen -- Rome -- Biography -- Early works to 1800.; Germanic peoples -- Early works to 1800.; Germanic peoples; Statesmen -- Rome -- Biography; Hommes d'État -- Rome -- Biographies -- Ouvrages avant 1800.; Germains -- Ouvrages avant 1800.; Germains; Hommes d'État -- Rome -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; HISTORY -- Ancient -- General; Germanic peoples; Statesmen; Rome (Empire); collective biographies; Early works; Biographies; Biographies; Biographies